Effects of Monetary Motivational Techniques on Organizational Performance of St. Benedict's Ndanda Referral Hospital – Ndanda Mission Masasi, Tanzania - Mbembela Mayala, Nyanjige; D. Njau, Simon; Onyancha, Hezron (International Journal of Scientific Research and Management (IJSRM), 2022)
The study is on assessment of the monetary motivational techniques on organizational performance of St. Benedict's Ndanda Referral Hospital in Mtwara Tanzania. The study was guided by the Two Factor Theory.  A concurrent research design was used whereas the research approach was mixed involving quantitative and qualitative data collection. A sample of 177 respondents was determined using Yamane (1964) from a target population of 316 employees of the Hospital. Content validity was ensured through discussion with specialists at the University and supervisors while reliability of the instruments was tested through Cronbach alpha coefficient. Data was collected through a self-administered questionnaire and key informant interviews using an interview guide. Quantitative data was analyzed using descriptive statistics where mean scores, frequencies and percentage were used to present results. Study findings indicated that salary, overtime, staff loans and health insurance with mean scores of 3.704, 3.654, 3,542 and 3.429 respectively as the highly rated monetary motivational factors used in the study area. Likewise, bonuses, transport allowances and gratuity were the least rated monetary techniques used with mean scores of 0.002, 0.003 and 0.001 respectively. From the study findings; it is concluded that there are monetary techniques that work effectively as indicated. It is thus recommended that the management of the hospital should look critically to other monetary motivation techniques in order to enhance the motivation of employees towards organizational performance of the hospital.